Ester prodrugs of cyclic 1-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]-5-azacytosine: synthesis and antiviral activity - Krecmerová, Marcela; Holý, Antonín; Pohl, Radek; Masojídková, Milena; Andrei, Graciela; Naesens, Lieve; Neyts, Johan; Balzarini, Jan; De Clercq, Erik; Snoeck, Robert (Journal of medicinal chemistry, 2007)
Reaction of 1-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]-5-azacytosine (1) with dicyclohexylcarbodiimide and N,N,-dicyclohexyl-4-morpholinocarboxamidine in dimethylformamide at elevated temperature afforded the corresponding cyclic phosphonate 2, that is, 1-{[(5S)-2-hydroxy-2-oxido-1,4,2-dioxaphosphinan-5-yl]methyl}-5-azacytosine. Compound 2 exerts strong in vitro activity against DNA viruses, comparable with activity of parent compound 1. Transformation of 2 to its tetrabutylammonium salt followed by reaction with alkyl or acyloxyalkyl halogenides enabled us to prepare a series of structurally diverse ester prodrugs: alkyl (octadecyl), alkenyl (erucyl), alkoxyalkyl (hexadecyloxyethyl), and acyloxyalkyl (pivaloyloxymethyl) (3-6). The introduction of an alkyl, alkoxyalkyl, or acyloxyalkyl ester group to the molecule resulted in an increase of antiviral activity; the most active compound was found to be the hexadecyloxyethyl ester 5. The relative configuration of the diastereoisomer trans-6 was determined using H,H-NOESY NMR.
Keywords: Cell Line; DNA viry; cytosin; estery; RNA-viry; Retroviridae; Stereoisomerism; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; virová léková rezistence; antivirové látky; Drug Resistance, Viral; Prodrugs; stereoizomerie; vztahy mezi strukturou a aktivitou; Humans; RNA Viruses; prekurzory léčiv; Cytosine; DNA Viruses; Esters; buněčné linie; Antiviral Agents; Structure-Activity Relationship; lidé